Die uittoetsing van 'Seven quickly administered tests of physical capacity' - Van Dyk, Nelle (Stellenbosch : Stellenbosch University, 2012)
Proefskrif (B. Ed. Ph.) -- Universiteit van Stellenbosch, 1943.